1806 Mass. Acts 121-22 - (:unkn) unknown (My University, 1806)
An Act Providing for the Punishment of the Crimes of Burglary, and Other Breaking and Entering of Buildings: Be it enacted by the Senate and House of Representatives, in General Court assembled, and by the authority of the same, That if any person, with intent to kill, rob, steal, commit a rape, or to do or perpetrate any other felony, shall in the night time break and enter, or having, with such felonious intent, entered, shall in the night time break a dwelling house, any person then being lawfully therein, and such offender being, at the time of such breaking or entering, armed with a dangerous weapon, or arming himself or herself, in such house, with a dangerous weapon, or committing an actual assault upon any person lawfully being in such house; every such offender, and any person present, aiding, assisting or consenting in such burglary, or accessary thereto before the fact, by counselling, hiring, or procuring such burglary to be committed, who shall be duly convicted thereof in the Supreme Judicial Court, shall suffer the punishment of death.
Keywords: CARRY - INTENT TO COMMIT CRIME